DIRECT REGENERATION FROM EMBRYO CULTURES OF LYCOPERSICON ESCULENTUM MILL CV PUSA RUBY - P. KARUNAKAR RAO, (International Journal of Pharma and Bio Sciences, 2014)
Embryos of Lycopersicon esculentum Mill cv Pusa Ruby cultured on MS medium supplemented with auxins such as IAA (1.0mg/l) and NAA (1.0mg/l) alone produced whole plantlets. However, embryos cultured on 2,4-D (1.0mg/l) produced callus with roots. BAP (1.0mg/l) and Kn (1.0mg/l) alone are able to induce shoots with callus. Among various combinations of auxins and cytokinins i.e., (1.0 mg/l) IAA + BAP (2.0 mg/l) and IAA (1.0 mg/l) + Kn (2.0 mg/l) gave good response and produced green nodular callus with shoots. Whereas, NAA (1.0mg/l) + BAP (2.0mg/l) and Kn (2.0mg/l) produced callus only. The combinations of IAA (0.5mg/L) + BAP (4.0 mg/L) was found to be better medium compared to all other concentrations of IAA + Kn medium analyzed.